PENELITIAN TERHADAP PUTUSAN HAKIM PERKARA NO. 09/G/2008/PTUN SMG GUGATAN MELAWAN GUBERNUR JAWA TENGAH - Lapon Tukan Leonard (Masalah-Masalah Hukum, 2010)
A change of concept of how to mange a state has been changed significantly last few decades. The change of concept from nachtwaker staat to the welfare state has been bringing a dramatic change in the Administrative Law itseif. The state (government) can not stay only in office, but must go and stay with the people in people's real lives. This brings the concequences that the frictions between the state and the people might be happened frenquently In this situation, the existence of an Administrative Court is considered important and urgent. This research is trying to analyse what is actually happened in the Administrative Court management, how it works, and why it does.